Presentation - Recio Dávila, Carlos (Sekkan Revista de Ciencias Sociales y Humanidades, 2026)
In this issue of Sekkan, the editorial committee has teamed up with Enrique Roberto Peralta Mazariego, research professor at the Technological University of Cancún, who served as guest editor. This collaboration has strengthened the experiences involved in the journal’s production process, from the call for papers, the reception and evaluation of articles, to the publication of this issue.Peralta Mazariego has focused his research work on the educational field in southeastern Mexico, particularly on technostress among students, the internationalization of higher education, and tutoring programs. In 2024, he was recognized with the Quintana Roo State Award for Humanities, Science, Technology, and Innovation for his research project on organizational sustainability.His work as guest editor has consolidated this issue of Sekkan, which brings together seven articles by authors from institutions in southeastern Mexico on topics related to education: ethical frameworks for AI, relational pedagogical mediation and technological automation, teaching competencies in telesecundaria, integrative coursework in professional training, university students in relation to economic violence and peace, academic tutoring, and institutional skills for agricultural logistics scaling in a specific community.We are certain that the quality of the articles, as well as their relevance and soundness, offer significant contributions to knowledge in the social sciences.